2020
DOI: 10.3899/jrheum.200307
|View full text |Cite
|
Sign up to set email alerts
|

Febuxostat Use and Risks of Cardiovascular Disease Events, Cardiac Death, and All-cause Mortality: Metaanalysis of Randomized Controlled Trials

Abstract: Objective To assess whether febuxostat use increases the risk of developing cardiovascular events, death from cardiac-cause and all-cause mortalities. Methods The relevant literature was searched in several databases including the MEDLINE (PubMed, 1 Jan. 1966–29 Feb. 2020), Web of science, EMBASE (1 Jan. 1974–29 Feb. 2020), ClinicalTrials.gov and Cochrane Central Register for Controlled Trials. Manual searches for references cited in the original studies and relevant review articles were also performed. All st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…We sincerely appreciate Dr. Kawada's comments in response to our metaanalysis. 1 We agree with most of these opinions and would like to clarify our views here.…”
Section: Dr Deng Et Al Replymentioning
confidence: 61%
See 1 more Smart Citation
“…We sincerely appreciate Dr. Kawada's comments in response to our metaanalysis. 1 We agree with most of these opinions and would like to clarify our views here.…”
Section: Dr Deng Et Al Replymentioning
confidence: 61%
“…4 Further, the doses of febuxostat intake were higher in the FAST trial. In our metaanalysis, 1 the pooled results indicated that the CV side effects of febuxostat were not significantly dose-dependent. Combined with a series of early clinical trial studies from Becker et al (ie, the CONFIRM trial 5 and FACT trial 6 ) as well as our metaanalysis, 1 febuxostat use was not associated with increased CV events and heart-related mortality.…”
Section: Dr Deng Et Al Replymentioning
confidence: 66%
“…In other words, this study observed the effects of febuxostat and allopurinol on the risk of cardiovascular disease under a condition in which both drugs were equally considered as first-line therapy in clinical settings. A recent meta-analysis study found that febuxostat use was not associated with an increased risk of cardiovascular events and death, all-cause mortalities [ 20 , 21 ]. In addition, febuxostat was found not to be associated with an increased risk of death or serious adverse events compared to allopurinol in a recent FAST (2020) study [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…I read the paper by Deng et al, 1 in which the authors conducted a metaanalysis to evaluate whether febuxostat use increased the risk of developing cardiovascular (CV) events, cardiac death, and all-cause mortality. The adjusted relative risk (RR) of febuxostat use for all-cause mortality was 0.87 (95% CI 0.57-1.32).…”
mentioning
confidence: 99%
“…I have 2 concerns about their study. 1 First, there are 2 clinical trials to compare the safety of allopurinol and febuxostat: the CARES trial and the FAST trial. 3,4 White et al concluded that "febuxostat was noninferior to allopurinol with respect to rates of adverse CV events.…”
mentioning
confidence: 99%